Fetal Biometry Nomogram Based on Normal Population : an Observational Study - Wibawa, Aria; Rumondang, Amanda (Indonesian Socety of Obstetrics and Gynecology, 2018)
Objective: To establish fetal biometry nomogram using percentilemethod based on normal population.   Methods: A descriptive retrospective study in order to establishfetal biometry nomogram using percentile method basedon normal population. Four fetal biometry measurement (BPD,HC, AC and FL) was collected from ultrasonography examinationresult in Fetomaternal Division Ultrasound Unit - AnggrekClinic and from medical record unit Dr. Cipto MangunkusumoGeneral Hospital, from January 2015 until April 2016. Databeing documented using case report form and being tabulatedusing Microsoft Excell 2011 Version 14.7.0 (161029). All datawere analyzed using SPSS 20.0 dan Matlab R2016a.   Results: There were 6169 pregnant women underwent fetalbiometry ultrasound within January 2015 - April 2016. Basedon inclusion criteria, 2798 (45%) were eligible as researchsample distributed from 12 until 42 wga. Due to evenly distributiondata, 2205 (78%) were distributed from 20 until 40 wgato develop fetal biometry nomogram. Most pregnant womenwere 28.9 years old (SD  5.74) in range of 21-30 (55%) yearsold. The youngest was 13 years old and the oldest was 45years old. Four fetal biometry were collected and distributedevenly using percentile method to establish fetal biometrynomogram. As for estimated fetal weight curve was developedby Hadlock C formula. Each biometry was calculated the 10th,50th and 90th centile curves according to gestational age. Thus,representing the fetal biometry and modified Hadlock C estimatedfetal weight nomogram based on normal population inJakarta.   Conclusion: Each biometry and modified Hadlock C estimated fetalweight were calculated in 10th, 50th and 90th centile curves accordingto gestational age represent fetal biometry nomogram based onnormal population in Jakarta. Keywords: biometry, estimated fetal weight formula, nomogram